2013
DOI: 10.1134/s1547477113020106
|View full text |Cite
|
Sign up to set email alerts
|

The thermodynamic properties of weakly interacting quark-gluon plasma via the one-gluon exchange interaction

Abstract: The thermodynamic properties of the quark gluon plasma (QGP ) as well as its phase diagram are calculated as a function of baryon density (chemical potential) and temperature. The QGP is assumed to be composed of the light quarks only, i.e. the up and the down quarks, which interact weakly and the gluons which are treated as they are free. The interaction between quarks is considered in the framework of the one gluon exchange model which is obtained from the Fermi liquid picture. The bag model is used, with fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…In Refs. [15,22,37], the authors found the entropy increases with increasing temperature for light quark, strange quark, and natural particles. We have the same conclusion for charm quark.…”
Section: Results and Discussion [41] Quarkonium Massesmentioning
confidence: 99%
See 3 more Smart Citations
“…In Refs. [15,22,37], the authors found the entropy increases with increasing temperature for light quark, strange quark, and natural particles. We have the same conclusion for charm quark.…”
Section: Results and Discussion [41] Quarkonium Massesmentioning
confidence: 99%
“…In Ref. [15], the quark -gluon plasma is assumed to be composed of the light quarks only such as the up and down quarks, which interact weakly, and the gluons which are treated as they are free. They found the free energy decreases with increasing temperature.…”
Section: Results and Discussion [41] Quarkonium Massesmentioning
confidence: 99%
See 2 more Smart Citations
“…[30,[38][39][40]. Several attempts have also been made to study the EOS for interacting QCD matter [31,32,34,36,41,42]. For example, new lattice results for the equation of state of QCD with 2 + 1 dynamical flavors were obtained in [41,42].…”
Section: Introductionmentioning
confidence: 99%